Consumer Protection Of Mobile Banking Users (Case Study Of Commonwealth Mobile Banking Account Breaking On Behalf Of Ilham Bintang) - Muhammad Ilham; Inosentius Samsul; Henny Marlyna (Faculty of Law, University of Mataram, 2022)
Bank services, in general, are services to store customer funds safely. As one of the bank's primary services, customers have the right to obtain guarantees for funds deposited in the relevant bank. In its development, bank services have used technology assistance to create a mobile banking product. In the case raised in this paper, some customers lose funds at the bank, where the funds are stored use mobile banking. The purpose of this paper is to review the applicable Indonesian laws following the case of Ilham Bintang, a consumer of Common Wealth Bank. This research shall use secondary data from the normative juridical, a process to find the rule of law, legal principles, and legal doctrines to answer the legal issue. The legal topic discussed in this paper is how the applicable laws of banking and consumer protection protect bank consumers specifically, regarding account break-ins. Based on Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking and Law Number 8 of 1999 concerning Consumer Protection, banks as business actors are required to provide compensation, damages, and reimbursement, if offered, are not according to what promise. However, if it proven that this is not the business actor’s fault, the business actor may be released from this responsibility.